Effectiveness of mobile health interventions for pregnant women with gestational diabetes mellitus: a systematic review and meta-analysis - Hui Xin Wei; Yi Ling Yang; Ting Yu Luo; Wei Qiang Chen (Taylor & Francis Group, 2023)
Gestational diabetes mellitus is a growing global health problem. Inadequate management during pregnancy can lead to maternal and foetal complications. Currently, mobile health (mHealth) delivers healthcare services, playing an increasingly important role in the management of blood glucose in GDM. This study aimed to systematically evaluate the effectiveness of mHealth intervention in pregnant women with GDM. Based on randomised controlled trials of mHealth application in GDM patients searched from the database, literature screening, data extraction, and quality evaluation were conducted independently by two researchers. Statistical analysis was performed using Review Manager 5.4 software. The review included 27 studies with a total of 3483 patients. The results showed a significant improvement in glycemic control. In addition, mHealth interventions could reduce the occurrence of adverse pregnancy outcomes and improve self-management ability. In a subgroup analysis, recording of delivery mode and WeChat combined phone call indicated significant differences with mHealth interventions. It was suggested that mHealth interventions imposed a positive effect on glycemic control and reduction of adverse pregnancy outcomes in GDM patients. Our results demonstrated that the application of mHealth interventions can act as an effective and feasible approach to self-management to promote the self-management level and awareness of GDM patients.